Leaping Forward in Green Transport : The Case of Korea - Lee, Changgi; Vandycke, Nancy L.; Sung, Nak Moon; Choi, Sang Dae; Yi, Eun Joo Allison; Lee, Sangjoo (World Bank, Washington, DC, 2015)
What do Bangkok, Cairo, Lagos, Mumbai, and Nairobi have in common? These megacities, like others in burgeoning emerging market economies, are magnets for people seeking better opportunities. They also suffer from serious traffic congestion, high levels of greenhouse gas (GHG) emissions, and heavy air pollution. These urban areas face a stark dilemma: economic expansion attracts more people and vehicles; but the resulting traffic and pollution hinder further growth while reducing the quality of life for their citizens. In spite of rapid growth, urbanization, and motorization, Korea has succeeded so well in expanding the use of public transport that it has stabilized energy consumption per capita in the road sector. In 2010, Korea took aim at a new 10-year goal with its green transport master plan: reduce GHG emissions by one-third while maintaining its competitiveness. To do so, Korea seems poised to create more cutting-edge transport innovations that can serve as models for other countries.